Higher Blood Lead Level Is Associated With Increased Likelihood of Abdominal Aortic Calcification - Qin, Zheng; Li, Hancong; Xu, Yingfei; Li, Jiameng; Su, Baihai; Liao, Ruoxi (Frontiers in Cardiovascular Medicine, 2021)
Aims: This study aimed to evaluate the association between blood lead level (BLL) and abdominal aortic calcification (AAC) in US adults aged ≥40 years. Methods: We obtained data from 2013-2014 National Health and Nutrition Examination Survey (NHANES). Participants who missing the data of BLL and AAC scores were excluded. BLL was measured using inductively coupled plasma mass spectrometry directly. AAC scores were quantified by Kauppila score system and severe AAC was defined as AAC score >6. Weighted multivariable regression analysis and subgroup analysis were conducted to explore the independent relationship between BLL with AAC score and severe AAC. Results: A total of 1530 participants were included with the mean BLL of 1.45 ± 1.31 ng/dL and mean AAC score of 1.40 ± 3.13. The prevalence of severe AAC was 7.98% overall and participants in higher BLL quartile showed higher prevalence of severe AAC (Quartile 1: 3.55%, Quartile 2: 7.28%, Quartile 3: 9.88%, Quartile 4: 12.58%, P<0.0001). BLL was positively associated with higher AAC score (β=0.15, 95%CI: 0.02, 0.27, P=0.021) and increased risk of severe AAC (OR=1.11; 95%CI: 1.00-1.22; P=0.047). Subgroup analysis and interaction test indicated that the association between BLL and AAC was similar in different population settings. Conclusions: Higher BLL was associated with higher AAC score and increased risk of severe AAC. Lead burden should be considered for people with AAC in clinical settings.